Internet-delivered Cognitive Behavioural Therapy - Richards, Derek; Enrique, Angel; Palacios, Jorge (Sage, 2019)
In recent years, computer-based and internet-delivered CBT (iCBT) has become an attractive and evidence-based alternative to face-to-face CBT, and in some cases, a significantly better option for some individuals. This chapter will discuss the origins of iCBT and the research that supports its efficacy and effectiveness, as well as the application of iCBT interventions in clinical practice. We will then explore the advantages and limitations of iCBT for service users and service providers, before considering the future of iCBT and its further expansion into clinical practice.
The Handbook of Brief Therapies: A Practical Guide
Keywords: Cognitive behavioural therapy; Internet-delivered CBT; Brief therapeutic interventions; Psychological treatments; ANXIETY; DEPRESSION; Mood and Anxiety Disorders; iCBT; internet-delivered interventions; Mental Health/Psychosocial disability